High-intensity zones in dogs with lumbosacral intervertebral disc degeneration: insights from MRI and histopathological findings - S. Amir Kamali; Michelle Teunissen; Dirk Hendrik Nicolaas van den Broek; Elisabeth M. Burgers; Guy C. M. Grinwis; Keita Ito; Marianna A. Tryfonidou; Björn P. Meij (Veterinary Quarterly)
The diagnosis and management of lumbosacral pain in dogs is challenging, requiring thorough examination, with MRI playing a crucial diagnostic role. This retrospective study investigates the presence of high-intensity zones (HIZ) in the dorsal annulus fibrosus (AF) of the lumbosacral region on MRI and describes the corresponding histopathological features in dogs with intervertebral disc (IVD) degeneration. T2-weighted (T2W) and T1-weighted (T1W) sagittal MRI scans were evaluated using a classification system developed in human medicine to analyze HIZ characteristics. Among 836 dogs with IVD degeneration, 57 (6.8%) exhibited T2W HIZ, with a median age of 7 years and median weight of 33.7 kg. All cases with HIZ consistently exhibited radiological degenerative lumbosacral stenosis. The most common T2W HIZ shape was round (43%), while 14% of lesions also appeared hyperintense on T1W. Histopathological analysis of 11 dorsal AF samples collected during standard-of-care decompressive surgery revealed two patterns: reactive cystic structures (3/11) and granulation tissue (8/11), with differential MRI presentation. This is the first study to document HIZ in the lumbosacral level of dogs with IVD degeneration. With this recognition, prospective analyses and their correlation with clinical presentations will be essential in determining the role and prognostic significance of HIZ.